1975
DOI: 10.1073/pnas.72.12.5130
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentrations of nonesterified arachidonic acid, 12L-hydroxy-5,8,10,14-eicosatetraenoic acid, prostaglandin E2, and prostaglandin F2alpha in epidermis of psoriasis.

Abstract: Lesional epidermis of psoriasis has a probable reduction in the cyclic AMP/cyclic GMP ratio. This altered ratio may in part be responsible for the characteristic glycogen storage, rapid cell proliferation, and reduced differentiation in lesional epidermis. The concentrations of prostaglandins E2 and F2alpha, free arachidonic acid, and 12L-hydroxy-5,8,10,14-eicosatetrawnoic acid in specimens of uninvolved and involved epidermis of psoriasis were measured with deuterium-labeled carriers and multiple ion analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
1
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(200 citation statements)
references
References 18 publications
6
192
1
1
Order By: Relevance
“…In various investigations we were able to show that the major part of neutrophil chemotactic activity in aqueous extracts of lesional psoriatic scales is due to a family of at least seven homologous polypeptides called anionic neutrophil-activating peptide (ANAP) (51), whereby one of the main components, termed N2-ANAP, is by NH2-terminal sequencing, identical with NAPAL-8 (52) . Therefore, it is intriguing to speculate that NAP/IL-8 could be a physiologically relevant activator of PMN-5-lipoxygenase when NAP/IL-8, together with exogenous AA, is present in large amounts in diseased tissue such as in psoriatic lesions (52,53).…”
Section: Resultsmentioning
confidence: 99%
“…In various investigations we were able to show that the major part of neutrophil chemotactic activity in aqueous extracts of lesional psoriatic scales is due to a family of at least seven homologous polypeptides called anionic neutrophil-activating peptide (ANAP) (51), whereby one of the main components, termed N2-ANAP, is by NH2-terminal sequencing, identical with NAPAL-8 (52) . Therefore, it is intriguing to speculate that NAP/IL-8 could be a physiologically relevant activator of PMN-5-lipoxygenase when NAP/IL-8, together with exogenous AA, is present in large amounts in diseased tissue such as in psoriatic lesions (52,53).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative Analyses of Prostaglandin E2, Prostaglandin F2, and Arachidonic Acid These analyses were performed by quantitative mass spectrometry as described previously for prostaglandins E2 and F l a [18] and for arachidonic acid [19]. Results of prostaglandin analyses were expressed as ng/ml culture medium (cf.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Diethyl ether in hexane eluted arachidonic acid whereas prostaglandin E2 and prostaglandin F2,, appeared in the combined ethyl acetate and methanol eluates. The compounds were methylated with diazomethane and purified by thin-layer chromatography as described before [19]. Prostaglandin EZ and F2?…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The monohydroxy metabolite of arachidonic acid, 8,10,, has been found in elevated levels in samples from lesional psoriatic skin, when compared to those from normal skin (Hammarstrom et al, 1975;Camp et al, 1983) and stereochemical analysis of psoriatic scale-derived 12-HETE has shown that the major stereoisomer present is 12(R)HETE (Woollard, 1986). Analysis of the biological activity of 12(R)-HETE has shown it to be a more potent chemokinetic agent for human neutrophils in vitro than the platelet product, 12(S)-HETE , Cunningham & Woollard, 1987Evans et al, 1987).…”
Section: Introductionmentioning
confidence: 99%